The Psychodrama and its Contribution to the Children’s Competitive Confrontation. Case Study - Zaragas C.K. (Moscow State University of Psychology and Education, 2021)
The purpose of this paper is twofold, first to study in depth by analyzing the phenomena in the circle of the psychodrama group and then to highlight the results from the application of the psychodrama tech¬nique to young athletes who would take part in competitions. A group of 6 boys and 4 girls (N = 10, 100%) aged 12 years ± 5 months have participated in psychodrama sessions, lasting 90 minutes, with a frequency of every 15 days for 12 months (January 2019 — January 2020). The meetings took place in parallel and in combination with the judo training that lasted 90 minutes for three times a week. Both the trainings and the psychodrama meetings took place in the same place. The present work is a case study for the detailed examination and qualitative analysis of the group of young judo athletes in the process of psychodrama. The results of the coupling of the program of physical education and the method of psychodrama were impres¬sive both by the testimonies of the children and the official results of the Panhellenic championship for girls and boys. Psychodrama can be an alternative method of education in school.